3y2+7y-6=0

Simple and best practice solution for 3y2+7y-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y2+7y-6=0 equation:



3y^2+7y-6=0
a = 3; b = 7; c = -6;
Δ = b2-4ac
Δ = 72-4·3·(-6)
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-11}{2*3}=\frac{-18}{6} =-3 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+11}{2*3}=\frac{4}{6} =2/3 $

See similar equations:

| 6x2-29x+20=0 | | 15+.50m=25+25m | | 3w2+49w+60=0 | | v2-5v-24=0 | | u2+6u-27=0 | | r2-16r+63=0 | | s(s+6)=48 | | s2+10s+21=0 | | 4q2-12q+9=0 | | y/20=70 | | 25p2+70p+49=0 | | m2-16m+64=0 | | k2+12k+36=0 | | -4h2-16h=0 | | 3f-81f2=0 | | 3d2-4d=0 | | 5c2+25c=0 | | a2+9a=0 | | 12(n-3)=4(n+1 | | 3x+2+0=3x+2+1 | | (5s+3)(2-s)=0 | | -12v-7+9v=26 | | (p+1)(p+2)=0 | | w-4/3+5=6 | | n^2-5n-300=0 | | 4(t-8)=3+6+2 | | 4(t-8)=6+2 | | -7(4x+5)=30 | | 3x+2x+1=5 | | s(s+12)=21 | | 20x^2+48x-19=0 | | 20x^2+48x+19=0 |

Equations solver categories